2022
DOI: 10.1108/ecam-07-2022-0668
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of emerging technologies on construction safety performance

Abstract: PurposeConstruction safety is heavily affected by using new technologies in this growing trend of technology adoption. Especially, safety performance is enhanced through the utilization of some effective technologies such as artificial intelligence, virtual reality, BIM and wearable devices. Therefore, the main purpose of this study is to investigate the influence of emerging technologies on construction safety performance and quantify the relationship between those. The proposed components of emerging technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 134 publications
(371 reference statements)
0
9
0
Order By: Relevance
“…The construction industry appeared to be one of the top industries referring to VR. The integration of VR in the construction field may aid in design visualization (i.e., providing the opportunity for designers to be immersed in their designs and make changes in real‐time), education and training, and remote collaboration (see Badamasi et al, 2022; Balali et al, 2020; Beh et al, 2022; Carreira et al, 2018; Davila Delgado et al, 2020; Dobrucali et al, 2022; Du et al, 2018; Fernandes et al, 2006; Getuli et al, 2021, 2022; Gu & London, 2010; Guray & Kismet, 2023; Han et al, 2006; Jacobsen et al, 2022; Ji et al, 2023; Omar & Mahdjoubi, 2022; Paes et al, 2021; Prabhakaran et al, 2022; Yan et al, 2022; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction industry appeared to be one of the top industries referring to VR. The integration of VR in the construction field may aid in design visualization (i.e., providing the opportunity for designers to be immersed in their designs and make changes in real‐time), education and training, and remote collaboration (see Badamasi et al, 2022; Balali et al, 2020; Beh et al, 2022; Carreira et al, 2018; Davila Delgado et al, 2020; Dobrucali et al, 2022; Du et al, 2018; Fernandes et al, 2006; Getuli et al, 2021, 2022; Gu & London, 2010; Guray & Kismet, 2023; Han et al, 2006; Jacobsen et al, 2022; Ji et al, 2023; Omar & Mahdjoubi, 2022; Paes et al, 2021; Prabhakaran et al, 2022; Yan et al, 2022; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another emerging trend is the use of VR for specialized occupational training. A considerable body of research is coalescing around the theme of on‐site safety training in construction, where VR has been proven to elevate safety metrics and overall performance (e.g., Dobrucali et al, 2022; Getuli et al, 2021; Guray & Kismet, 2023; Jacobsen et al, 2022; Ji et al, 2023; Yan et al, 2022; Zhang et al, 2022). Moreover, in specialized training programs such as aviation, there is a growing use of VR simulations to help pilots confront and manage their fear of heights, further enriching their training experiences and enhancing mental preparedness (e.g., Desai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The innovations introduced during the Industry 4.0 era constitute a major benefaction in construction safety management (Yap et al, 2022a, b;Zhou et al, 2013). Recently, Dobrucali et al (2022) composed a structural model of emerging technologies and safety performance indicators to reveal that construction safety performance is positively and significantly associated with the utilization of some effective emerging technologies. In another study, Forcina and Falcone's (2021) systematic literature review on Industry 4.0 enabling technologies revealed that technological transformation in construction safety management significantly developed a higher competency level as compared with the conventional approach.…”
Section: Introductionmentioning
confidence: 99%
“…This technology is extensively used to estimate the volume of completed works and to determine the site’s progress [ 5 ]. BIM can enhance construction safety performance with its collaborative and cooperative environment and information-sharing mechanism [ 6 ]. To conduct a volumetric analysis of stockpiles, the three-dimensional (3-D) method is a more prevalent and advanced way [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A statistical analysis of the results showed that UAVs and TLSs are similar, especially in an undisturbed canopy, and different in smoothness and preciseness. UAVs were found to generate smooth data and were less precise than TLSs [ 6 ]. Similarly, Cunha et al [ 17 ] investigated the suitability and accuracy of drones and laser scanners in a sizeable outdoor crime scene at a parking lot in Brazil.…”
Section: Introductionmentioning
confidence: 99%